Dance as treatment therapy in breast cancer patients – a systematic review - Boing, Leonessa (2017)
This systematic review aimed to identify and analyse articles which investigated the influence of dance as adjuvant therapy in breast cancer. The selected databases were PsycInfo, PubMed, The Cochrane Library, ScienceDirect and the Virtual Health Library (VHL). The following descriptors were considered for the selection of articles: [dance therapy] OR [movement therapy] OR [complementary therapies] AND [breast cancer] OR [cancer neoplasms] OR [breast tumor] OR [breast carcinoma] present in the titles or abstracts of the articles. The quality of the data was evaluated by means of the methodological criteria proposed by Downs and Black. Eleven articles were found. The approach followed in methodologies were dance therapy movement, Greek dance, Sacred dance, ballroom dance, classical ballet and jazz. Favorable results were found for self-image, femininity, mood, self-esteem, physical well-being, perceived stress, pain, consciousness, depression, couples trust, anxiety and fear. It was observed better range of motion and strength in upper limp, and also improvement in functional capacity. The authors pointed dance as an effective alternative adjuvant treatment in breast cancer. Dance promotes psychological benefits in women in breast cancer, as well as improvements in upper limbs. Future studies are recommended with best scientific evidence, in order to investigate interventions with dance during other treatment and disease stage and with other forms of dance.